(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Aravind Adiga’s second book Between the Assassinations is a collection of thirteen stories where the locale is kittur- an imaginary Malgudi (R K Narayan) type town, a microcosm of whole India. Here, I have made a quick survey of a few stories from the book. They highlight Adiga’s deep disgust over at the stinging and stinking evils of rampant communalism, corruption, castism and the inhuman police atrocities meted out to the low caste people. The cruel mindset of the upper caste people who would not tolerate the idea that a scavanger’s son should not dare to stand up before them.